Elementary school with violence from the troupe: each other and things - Mora-Rosales, José (2019)
The research revolves around the purpose of understanding from the triad one-on-one and things the realities present in a Venezuelan elementary school immersed in communities with different levels of violence. The method of hermeneutic phenomenology was used, with targeted interviews and content analysis, emerging categories and triangulating information.  The findings from the Other are: cultural violence, intolerance and recognition of diversity, from Things: Values and Role of teacher and family and from the One: Culture and Ancestral Values, Affective Communication. It is concluded that domestic, cultural and school violence are present as they shape the young person into an aggressive and intolerant citizen. Recognition of the role of the family and educator as a promoter of the principles of peace, from a ousía of their actions, are constituted in a challenge of practice of peace, then the position of the social common is framed by a collective violence of the domination of things.